50km race walking tactics at world championships and Olympics - Kisiel, K.; Kisiel, J. (Slovak Journal of Sport Science, 2017)
This study is an attempt at determining the tactics of 50km race walking in the most important sport events, based on the analysis of 5km lap times. The analysis covers lap times of finalists at the World Championships in Moscow and Beijing well as the Olympics Games in London and in Rio de Janeiro, and also distribution of lap times of the gold medallist from the Olympic Games in Rio de Janeiro, Matei Toth, during the analysed four competitions. Findings: The conducted analysis indicates that the speed at which a distance is covered generally increases until 40km, while the last 10km have no major impact on changes in the final classification. Attention has been paid to the very important role played by mental resilience. The authors anticipate, based on the presented findings and trends that occur in contemporary sport, that the distance will be changed to 45km at the next Olympics in Tokyo.